Efecto de diferentes densidades de siembra y control fitosanitario en fréjol caupí (Vigna unguiculata, L Walp), en Manglaralto Provincia de Santa Elena - Alejandro Salinas, Iván Francisco (2017)
The research was conducted in Manglaralto, in the practice center of the State University of Santa Elena Peninsula (UPSE), during the period of October 2016 to January 2017. We assessed the effect of different densities of planting and phytosanitary control in Beans Cowpea (Vigna unguiculata, L Walp), due to the incidence of pests and diseases that attack the crop. For this we used a design of divided plots, considering the factor to three phytosanitary controls and the factor B three sowing densities, with four replicates. The variables studied of the different insecticides factor A were measured through the different agronomic variables where the analysis of the variance, determined that there was a significant effect on the densities of sowing with respect to germination, the Flowering and ripening were presented at 45 and 62 days, plant height 15-60 days and pods per plant presented highly significant effect on factor A. Pod length both factors were significant. Seeds per pod There was significant effect on factor A. In the yield Kg/ha There was significant effect on factor A and factor B highly significant. The largest production of pods, obtained the density 83 333 plts/ha with average of 4 000 kg/ha, pertaining to the treatment (T4) in application of the botanical insecticide Neem-x0.40 CE. The second place of performance was located the treatment (T7) with 2812.45 Kg/ha, in application of the biological insecticide Piretrin and that also resulted with better economic profitability. Thirdly the treatment (T5) with 2457.47 kg/ha. From the above we can say that higher densities of sowing performance is higher.